Determinants of The Use of Digital Service at Islamic Banks: The Role of Technology and Transaction Costs - Agustin, Rohmi Maulina; Hidayanti, Nur Fitri; Aini, Nur (Universitas Islam Kadiri, 2026)
This study aims to analyze the effect of technology application and transaction costs on the decision to use Islamic bank digital services in Mataram City. The research method uses a quantitative approach with an associative survey, involving 100 respondents selected through random sampling with the criteria of active customers using digital services. Data were collected using a closed-ended questionnaire with a five-point Likert scale and analyzed using SPSS through descriptive statistics and multiple linear regression tests, including the F test, t test, and coefficient of determination (R²). Descriptive results showed an average value of technology adoption of 83.51%, transaction costs of 79.82%, and usage decisions of 80.23%. However, regression results indicated that the two independent variables did not have a significant effect on usage decisions, with an F test significance value > 0.05 and R² of only 2.7%. These findings indicate that customer decisions are influenced by factors outside the research model. This study concludes that technological improvements and cost efficiency have not been able to directly encourage the use of digital services. The implication is that Islamic banks need to strengthen security, service quality, application convenience, and user trust to increase the use of digital services.